2012
DOI: 10.4103/2277-9175.100153
|View full text |Cite
|
Sign up to set email alerts
|

Prospective utility of therapeutic ultrasound in dentistry-Review with recent comprehensive update

Abstract: Background:The utility of ultrasound (US) for therapeutic purposes is still in its infancy. Therapeutic US (TUS) has been used widely in medical field for urological application, surgical intervention, bone healing, and osteointegration in cancer and healing of full thickness excised skin lesions, and within dentistry as a prediagnostic, diagnostic and therapeutic purpose. The purpose of the paper is to review and determine the efficacy of US as one of the treatment modalities for its role in maxillofacial reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…These findings are similar to those reported by Rai et In the present study, the US treatment protocol dose was set at 1 W/cm 2 /1 MHz/5 minutes/every day until 20 sessions of treatment were completed. This is in accordance with the dose proposed by Rai et al (22) (0.5 -1 W/cm 2 /3 MHz/5 min duration) for anti-inflammatory effect. Rai et al (22) stated that lower doses (0.1 -0.6 W/cm 2 ) should be used in acute states, whereas higher doses (0.3 -0.8 W/cm 2 ) must be used for chronic states.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are similar to those reported by Rai et In the present study, the US treatment protocol dose was set at 1 W/cm 2 /1 MHz/5 minutes/every day until 20 sessions of treatment were completed. This is in accordance with the dose proposed by Rai et al (22) (0.5 -1 W/cm 2 /3 MHz/5 min duration) for anti-inflammatory effect. Rai et al (22) stated that lower doses (0.1 -0.6 W/cm 2 ) should be used in acute states, whereas higher doses (0.3 -0.8 W/cm 2 ) must be used for chronic states.…”
Section: Discussionsupporting
confidence: 92%
“…Rai et al (22) and Mishra et al (23) have stated that no single treatment is more effective than any other for the management of TMJD. However, they state that any treatment modality (US, LASER, short-wave diathermy, and pulsed short-wave diathermy) is better than placebo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency used is between 1.0 and 3.0 MHz. [ 12 13 ] It is known to accelerate healing, decrease joint stiffness, alleviate pain, increase the extendibility of collagen fibers, and reduce muscle spasm. [ 14 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…The present study ran concurrently with a one conducted by Rai et al [35]; they reported that therapeutic ultrasound is effective in the treatment of maxillofacial disorders through lessening pain and enhancing the healing property of soft tissues.…”
Section: Discussionmentioning
confidence: 90%